Uptake of a microcomputer database package to assist livestock management decisions in Africa - Wissocq, N.M.; Durkin, J.W.; Trail, J.C.M.; Gettinby, George; Bell, R.J.; Berhane, H.; Light, D.E. (Elsevier, 1989)
Provides a brief history of the developmet of IDEAS (the ILCA Data entry and Analysis system) and presents findings from a questionnaire recently used to users to assess the uptake of IDEAS in African Production systems during the first years of its release.